The acceptability and feasibility of a planned pre-pregnancy weight loss intervention (the Plan-it Study): A Protocol Paper. Issue 1 (2021) - Coulman, Elinor; Cannings-John, Rebecca; Couzens, Zoe; Davies, Freya; Henley, Josie; Lau, Mandy; Lugg-Widger, Fiona; Morantz, Leah; Sanders, Julia; Scherf, Caroline; Strange, Heather; Channon, Susan
No abstract available